Causes and outcomes of revision surgery in subjects with pulsatile tinnitus - Shim, Ye Ji; Lee, Hanju; Park, Sung-Min; Kim, Dohee; Koo, Ja-Won; Song, Jae-Jin (Frontiers in Neurology, 2023)
Introduction Once the underlying pathology has been identified, pulsatile tinnitus (PT) can be treated successfully with surgical or interventional management. However, some patients experience residual or recurrent symptoms following initially successful surgical treatment, and require revision surgery or additional procedures. Here, we report a case series of patients who had undergone revision surgery or interventional treatment, and suggest possible ways of minimizing the need for revision. Methods Between January 2014 and March 2023, a total of seven subjects underwent revision surgery or interventional treatment for persistent or recurrent PT after initial surgical treatment. Demographic data, reasons for revision, and changes in symptoms before and after revision were analyzed retrospectively. Temporal bone computed tomographic angiography images were reviewed to identify the causes and reasons for revision. Results Of the seven subjects, six underwent sigmoid sinus (SS) resurfacing/reshaping due to ipsilateral diverticulum (Div) or dehiscence (Deh), and one underwent jugular bulb (JB) resurfacing due to a high-riding JB with bony Deh. Of the five subjects who underwent revision SS surgery due to recurrent SS-Div or SS-Deh, three showed marked resolution of PT, while the other two showed partial improvement of the symptoms. One subject who underwent revision JB resurfacing, and another who underwent additional transarterial embolization for a concurrent ipsilateral dural arteriovenous fistula, reported marked improvement of PT. Discussion The possibility of recurrence should be taken into account when performing surgical intervention in patients with PT. The likelihood of recurrence can be minimized through a comprehensive evaluation to identify possible multiple etiologies, and through the use of durable materials and appropriate surgical methods.